Effect Of Aerobic Versus Resistive Exercise On Restless Leg Syndrome In Hemodialysis Patients (International Journal of Environmental Sciences, 2025)
Background: Hemodialysis (HD) patients typically have a variety of negative consequences, including restless leg syndrome (RLS), which can be caused by the medical procedure or the end stage of renal failure. Exercises like resisted exercise and stationary aerobic cycling can help relieve HD-associated symptoms. Aim: The effectiveness of aerobic versus resisted exercise on RLS severity in HD is unknown, so this study aimed to assess this aim. Methods: Sixty non-obese HD patients (from both sexes) patients with RLS were allocated from the Hemodialysis Unit of a Local General Hospital in El-Behirah Governorate. All patients were a regular HD therapy more than one year. The International Restless Leg Syndrome Study Group (IRLSSG) questionnaire was used to diagnose RLS in the affected HD patients. Ages of patients ranged from 35-45 years old. Patients were randomly and equally assigned into 2 groups: group A and group B, n = 30 patients for each group. Both groups received stretching exercise, massage program, and usual medical care for 12 weeks. Additionally, group A (n=30) received moderate-intensity intradialytic 30-miunte aerobic exercise (cycling of lower limbs) using horizontal cycle ergometer during the first two hours of dialysis, three times weekly. Group B (n=30) received 30-minute resistance exercises for lower limbs using ankle free weights for 30 minutes, during the first two hours of dialysis session, three times weekly. Outcome: RLS severity was assessed via IRLSSG questionnaire before and after 12 weeks. Results: Both forms of exercise significantly improved RLS severity in the two groups but the improvement was greater in group A. Conclusion: It could be concluded that both forms of exercise, aerobic or resisted exercise, improve RLS complaints in HD patients, but aerobic exercise recorded the highest improvement in RLS severity.